The balance between rhizosphere carboxylates and arbuscular mycorrhizal symbiosis in wheat phosphorus acquisition - Pu, Zitian; Zhang, Ruifang; Zhang, Chi; Wang, Hong; Wang, Xin-Xin (BMC plant biology, 2025)
Changes in plant growth and root traits in wheat (Triticum aestivum L.) vary depending on the level of phosphorus (P) supply. Two important strategies for P acquisition in wheat are the release of carboxylates into the rhizosphere and the presence of arbuscular mycorrhizal fungi (AMF). However, the relationship between root exudates and P concentration in the shoot and root, as well as the role of AMF in this process, is not yet fully understood. This study was conducted utilizing three P supply rates (0, 50, and 200 mg P kg soil) in conjunction with AMF inoculation. We examined the effects of AMF on amount of rhizosphere carboxylates and plant P uptake for nine P contrasting wheat genotypes. AMF decreased carboxylates, root biomass, root P content of wheat, and AMF reduced wheat root P allocation of wheat under all P levels. Notably, at 50 mg kg P level, the shoot P concentration of AMF-inoculated wheat exceeded that of other P levels, having a positive mycorrhizal responsiveness in all wheat genotypes. Furthermore, analysis revealed that wheat root morphology and acid phosphatase activity significantly influenced mycorrhizal growth responsiveness, while root carboxylates played a significant role in mycorrhizal P responsiveness. The P acquisition of wheat was found to be contingent upon the interplay of root morphology, AMF, and carboxylate levels, with AMF and carboxylate playing a more crucial role in enhancing P absorption. Consequently, the current research provides important insights for nutrient management in wheat agricultural cultivation.